Toward a business intelligence framework for e-government interoperability: data integration and decision support - Oumkaltoum Barakat; Omar Elbeqqali; Loqman Chakir (Institute of Advanced Engineering and Science, 2026)
In e-government systems, achieving smooth data interoperability is still a major challenge, especially in judicial systems where fragmented data management affects decision-making and service quality. In order to facilitate real-time data integration and interoperability, this paper suggests a novel service-oriented business intelligence (SOBI) framework coupled with a common central data warehouse (CCDW). Our approach, which uses the Moroccan legal system as a use case, makes use of materialized views and extract, transform, and load (ETL) procedures to guarantee scalable, secure, and efficient exchange of information between disparate systems. The framework provides a scalable model for e-governance while improving decision support, transparency, and service delivery. Findings highlight enhanced system performance and data sharing, with implications for broader e-government applications. The proposed approach provides a foundation for future extensions toward internet of thing-based urban planning and real-time data integration for smart and sustainable urban ecosystems.